Citizenship-in-nature? Exploring hazardous urbanization in Nova Friburgo, Brazil. Issue 99 (February 2019) - Coates, Robert
Highlights: Urban political ecology widens citizenship studies' scope. Nova Friburgo's urban development is linked to control over nature. Hazards and disasters are internal to urbanization processes. Failure of hazard containment calls forth liberal rights and responsibilities. 'Better citizenship' in an essentialised city reproduces hazardous environments. Abstract: This article explores the relationship between understandings of citizenship and the nature of hazardous urbanization. Through discussion of the colonial creation of a Brazilian city in the Atlantic Forest, and the concurrent creation of vulnerability to floods and landslides, it suggests that calls for 'better' citizenship—without a fundamental reappraisal of its ecological content—are likely to reproduce hazardous urban environments. The article aims to bring work from citizenship studies and urban political ecology into productive dialogue through a provocative case study, in order to explore the overlaps between the power of the modern, liberal, state and visions of nature as 'outside' the city.